Burden of Post-COVID-19 Hair Loss among Older Adults in Vietnam - Nguyen, Thi Hong Chuyen; Le, Hoang Thien; Nguyen, Thanh Huan (Tạp chí Y Dược Huế, 2023)
Background: Little is known about the burden of hair loss following coronavirus disease 2019 (COVID-19) infection in older adults. This study investigated the prevalence and associated factors of hair loss in older outpatients in Vietnam. Materials and methods: Between March 2022 and July 2022, this multicenter cross-sectional study included 547 older patients (aged ≥ 60 years; mean age 68.5 ± 6.9 years; men 27.1%) from three post-COVID-19 clinics. Factors associated with hair loss were assessed using logistic regression. Results: In total, 63 patients (11.5%) experienced hair loss. All of the patients with hair loss exhibited diffuse type. In the adjusted model, factors associated with hair loss were women (odds ratio [OR], 3.36; 95% confidence interval [CI], 1.43 - 7.89; P = 0.005), single or divorced in marital status (OR, 3.27; 95% CI, 1.33 - 8.02; P = 0.01), and history of COVID-19 related hospitalization (OR, 5.17; 95% CI, 2.44 - 10.95; P < 0.001). Conclusion: Our study found a substantial prevalence of post-COVID-19 hair loss in older outpatients.